SKRINING FITOKIMIA DAN UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN RACUN AYAM (Brucea javanica [L.] Merr.) ASAL KALIMANTAN SELATAN - Sutomo Sutomo; Fahriah Fahriah; Arnida Arnida (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Racun ayam is one of the plants which has several activities in its fruits, one of which is an antibacterial. This study aims to determine the antibacterial activity of ethanol extract of racun ayam leaves. The extraction was done by maceration method using ethanol as a solvent. Antibacterial activity assay was carried out on S. aureus, E. coli, and P. aeruginosa bacteria by disk diffusion method at the concentrations of 80, 100, and 120 ppm. The results showed that the ethanol extract of B. javanica leaves had the greatest inhibition zone on E. coli with inhibition zone diameter values ​​at 80, 100, and 120 ppm were 11.7 mm, 14.5 mm and 19.67 mm respectively. Inhibition zones in S. aureus could only be seen at 100 and 120 ppm which had inhibition zone diameters at 1.17 mm and 2.17 mm respectively, whereas in P. aeruginosa they did not have any inhibitory zone values. The results of statistical analysis showed a significance of the inhibition zone diameter values ​​of E. coli bacteria starting at 80 ppm with a sig value of 0.034. Due to a sig value was <0.05, it was categorized as significantly different from the negative control. The bacteria of S. aureus which had ​​<0.05 for sig values only found on 100 ppm and 120 ppm. Bacteria P. aeruginosa which had sig value >0.05 was not significantly different at all concentrations